Trichoderma in the promotion of growth and nutrition of dwarf cashew rootstock - Marcos Rodrigues dos Santos, João (Revista Ciência Agronômica, 2021)
Inoculation of microorganisms in plants performs important functions related to plant growth and nutrition. The responses are based on hormonal stimulation and improved absorption and effi ciency in the use of nutrients. Thus, the objective of this study was to evaluate the ability of Trichoderma strains (T. longibrachiatum and T. asperellum) to promote growth and improve the nutrition in dwarf cashew rootstock. The experiment was conducted in a shade net house with 50% of shading located in the Experimental Field of Pacajus, belonging to Embrapa Agroindústria Tropical, in Pacajus/CE, Brazil. The experimental design used was completely randomized, with three treatments and ten replicates. Each experimental unit consisted of a tube with a 288 cm3 capacity containing one seedling of dwarf cashew. At sixty days (60) after germination, the plants were evaluated for biometric parameters, Dickson’s quality index, and nutritional diagnosis of leaves. To verify the growth-promoting mechanisms, the strains were reisolated by indirect plating of roots. Nutrient accumulation in the leaves was not infl uenced by the application of the isolates; however, the seedlings were adequately supplied. The strains showed similarities in relation to growth-promotion mechanisms. The Trichoderma longibrachiatum strain promoted an increase in the growth, so its use as a supplement for the planting substrate is recommended.